Embodied Empowerment: Somatic Approaches to Gender Violence and Trauma - Brigden, Noelle (Violence against women, 2025)
This special issue brings together recent research on embodiment and practitioner-based somatic approaches to examine trauma and healing from violence. Contributors address the long-term somatic impact of oppression and the effects of structural inequalities enacted and perpetuated through bodies and in interaction with other bodies. Somatic practices and embodiment are addressed through the lens of intergenerational trauma, gendered, racialized, political, and colonial violence, and interpersonal and collective trauma. The introductory article contextualizes embodied empowerment, collective healing, and activist-research possibilities.